Synthesis and Antibacterial Activity of 1,3,5,7-Tetrahydroxy-9,10-Anthraquinone and Anthrone Derivatives - Siti Nurbayti; Didin Mujahidin; Yana Maolana Syah (Jurnal Kimia Valensi, 2022)
In this research, the synthesis of 1,3,5,7-tetrahydroxy-9,10-anthraquinone (1) and two anthrone derivatives, 1,3,5,7-tetrahydroxy-10H-anthracene-9-one (2) and 1-hydroxy-3,5,7,9-tetramethoxyanthracene (3) has been done. Compound 1 was synthesized by a symmetrical condensation reaction of 3,5-dihydroxybenzoic acid in concentrated sulfuric acid. Reduction of the carbonyl group in compound 1 with SnCl2/HCl-HOAc affords compound 2. Compound 3 was prepared by modifying the hydroxy groups of compound 2 by a methylation reaction. The synthesized compounds were identified using nuclear magnetic resonance spectroscopy (NMR) and a high-resolution mass spectrometry (HR-ESI-MS). The antibacterial activity test of the synthesized compounds against four pathogenic bacteria, Bacillus subtilis, Staphylococcus aureus, Escherichia coli, and Salmonella typhi, was carried out using the microdilution method. Compound 3 showed moderate activity against B. subtilis, E. coli and S. typhi with a MIC value of 37.5 µg/mL. Moderate activity was also shown by compound 2 against S. aureus, while compound 1 showed weak activity with a MIC value of 75 µg/mL against the four test bacteria.